Shared heritability and functional enrichment across six solid cancers - Xia Jiang (Nature Portfolio, 2019)
Similarities in cancers can be studied to interrogate their etiology. Here, the authors use genome-wide association study summary statistics from six cancer types based on 296,215 cases and 301,319 controls of European ancestry, showing that solid tumours arising from different tissues share a degree of common germline genetic basis.